The Influence of Satisfaction and Compensation on Employee Performance at Hotel Peninsula Palembang - Anggi Prissilia; Juhaini Alie; Muhammad Kurniawan DP (International Journal of Marketing & Human Resource Research, 2023)
The objective of this study is to analyze the effect of satisfaction and compensation on employee performance at Hotel Peninsula Palembang. The data collection technique in this study was by questionnaire and obtained a total sample of 55 employees. The data analysis used is multiple linear regression analysis model. The test results indicate that satisfaction (X1) has a significant effect on employee performance (Y). While compensation (X2) partially significant effect on employee performance (Y). The test results also show that satisfaction (X1) and compensation (X2) simultaneously have a significant effect on employee performance. This research is expected to be taken into consideration by the company to improve the performance of its employees.